L-lactic acid fermentation condition with rapid saccharification solution of total cellulose from wheat straw as carbon source - PENG Hongcao, XU Xueqin, WANG Xiaofan, ZHU Huixia, MA Xiaojing, YAO Risheng, WANG Huai (Zhongguo niangzao)
Using the saccharified liquid of wheat straw total cellulose hydrolyzed for 5 h as the alternative carbon source, the fermentation conditions of L-lactic acid produced by Bacillus coagulans were optimized by single factor and response surface tests. The results showed that the optimal fermentation conditions were seed age 4.20 h, inoculum 5%, fermentation temperature 50 ℃, loading liquid volume 42% and rotation speed 150 r/min. Under the optimal conditions, the yield of L-lactic acid was 54.92 g/L after 18 h fermentation. Therefore, the saccharified liquid obtained by rapid saccharification of wheat straw total cellulose could be used as the carbon source for L-lactic acid fermentation, which could replace grain starch to produce lactic acid. This research result would strongly promote straw lignocellulose to replace grain starch for lactic acid fermentation.